Plant Introduction Bureau of the Institute of Plant Industry and its relations with France in the 1920–1930s (based on the documents from the Central State Archive of Scientific and Technical Documentation of St. Petersburg) - E. S. Khablova (Труды по прикладной ботанике, генетике и селекции)
This article examines French–Soviet scientific cooperation focusing on the example of interactions between the Plant Introduction Bureau of the Institute of Plant Industry and French seed production companies. Objectives of the Bureau and the scope of its plant introduction activities are shown. Despite the importance of the Plant Introduction Bureau, its work encountered a number of obstacles. For example, the seed exchange was impeded by organizational problems, such as the neglect of delivery terms by the USSR Trade Office in France or by transport companies, and by financial constraints. There were also ideological conflicts, initiated by A. K. Kol and later by G. N. Shlykov, the heads of the Plant Introduction Bureau. Moreover, scientific links between the USSR and France were aggravated by the political situation in the world, where the USSR and France could not be regarded as allies. Despite these problems, the period from 1926 through 1933, when Nikolai Vavilov was Director of the Institute of Plant Industry, is considered the most productive in terms of cooper cooperation between the Plant Introduction Bureau and French seed production companies.